TINGKAT DISTORSI HARMONISA PADA LAMPU ESSENSIAL YANG BERBEDA MERK - Luqman Assaffat (PSTE UNIMUS, 2010)
Essential Lamp (SL) is a type of low pressure mercury lamp that worl<s leimlecittirnogn st hines icduer rtehnet tfuubnec atinodn .u Bsiencga uqsne e olefc trtohneic w sowriktcinhg e pqrLinipcmtpinlet , atsh ea ereispelanocsnei amthl eeln adtm isbpcah llcaasargtn ef o boerf classified as a non-linier electrical load It is callIend t hhea remleocntricics .p oHwaermr soynsitcesm ,a rae nmonu lltiinpel_easr olofathdesf rweiqll upernodcyu coe fa na feulnecdtarimcael iptaolwfreerq puoelnluctyio no.f wave. Harmonics generated by tlrc non-linier loads that - power system. So the harmonics will be able to disrupt thwe ipllo owrelur *qiutoatli